Energy flexibility in aerospace manufacturing: the case of low carbon intensity production - Haddad, Yousef; De Bonneval, Elena Galigny; Afy-Shararah, Mohamed; Carter, Joseph; Artingstall, James; Salonitis, Konstantinos (Elsevier, 2024)
In this paper, the prospects of energy flexibility in mitigating the environmental impact of aerospace manufacturing are explored. In collaboration with a UK-based aerospace manufacturing enterprise, demand response, in particular production time, is explored under different stochastic scenarios. This is done through a decision-support framework that consists of a stochastic discrete-event simulation model that tests different scenarios under a full factorial design of experiments framework. The simulation model tests various improvement strategies pertaining to prioritisation rules, production start-up rules, and operating hours. The model aids in scheduling energy-intensive processes, so the time of performing such processes can coincide with times of the day when the energy’s carbon intensity is at its lowest. The use case constitutes a family of aluminium structural aerospace components that are characterised by high production rate. Results demonstrate promising potential of the proposed approach, with the best-case scenario resulting in a 7% reduction in CO2e emissions. Analysis of the results demonstrate that operational decisions that do not require infrastructural changes or capital expenditures can contribute favourably to achieving net-zero targets. This research offers useful insights on leveraging operational short-term decisions to meet the aerospace manufacturing’s sector decarbonisation targets.
Keywords: Sustainable manufacturing; Energy flexibility; Demand response; Aerospace manufacturing; Discrete-event simulation